Use of amniotic membrane and autologous serum eye drops in Mooren’s ulcer - Lavaju, P; Sharma, M; Sharma, A; Chettri, S (Nepalese Journal of Ophthalmology, 2013)
Introduction: The management of Mooren’s ulcer can be a challenge for clinicians. Objective: To report a case of Mooren’s ulcer treated with amniotic membrane transplantation supplemented with autologous serum eye drops. Case report: A 22-year-old male presented with history of pain, redness, watering and diminution of vision of the right eye for one year. Examination of his eyes revealed the best corrected visual acuity ( BCVA) of 6\60 and 6\6 in his right and left eyes respectively. Slit -lamp examination of the right eye showed a peripheral ulcer extending from 2’0 to 11’0 clock positions with peripheral thinning and the features suggestive of Mooren’s ulcer. The condition did not improve with topical steroids and cyclosporine A eye drops. Therefore, 360 degree conjunctival peritomy with cauterization of the base was performed. Since there was no obvious improvement, the amniotic membrane transplantation was done with supplementation of autologous serum eye drops 20% four times a day. The patient showed symptomatic improvement in a week. There was cessation of the progression of the ulcer and decreased vascularization. One month later, a small corneal perforation was noted and was managed well with cyanoacrylate glue and bandage contact lens application. At nine months of follow up, the patient was symptomatically better, the ulcer had healed, the vascularization had decreased and the anterior chamber was well formed. Conclusion: Amniotic membrane transplantation showed to be promising in treatment of Mooren’s ulcer refractory to immunosuppressive therapy. Addition of autologous serum eye drops seems to be an effective supplementary therapy. Nepal J Ophthalmol 2013; 5(9):120-123 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7839